Genome-Wide Identification and Functional Characterization of the Trans-Isopentenyl Diphosphate Synthases Gene Family in Cinnamomum camphora - Yang, Zerui; Xie, Chunzhu; Zhan, Ting; Li, Linhuan; Liu, Shanshan; Huang, Yuying; An, Wenli; Zheng, Xiasheng; Huang, Song (Frontiers in Plant Science, 2021)
Trans-isopentenyl diphosphate synthases (TIDSs) genes are known to be important determinants for terpene diversity and the accumulation of terpenoids. The essential oil of Cinnamomum camphora, which is rich in monoterpenes, sesquiterpenes, and other aromatic compounds, has a wide range of pharmacological activities and has therefore attracted considerable interest. However, the TIDS gene family, and its relationship to the camphor tree (C. camphora L. Presl.), has not yet been characterized. In this study, we identified 10 TIDS genes in the genome of the C. camphora borneol chemotype that were unevenly distributed on chromosomes. Synteny analysis revealed that the TIDS gene family in this species likely expanded through segmental duplication events. Furthermore, cis-element analyses demonstrated that C. camphora TIDS (CcTIDS) genes can respond to multiple abiotic stresses. Finally, functional characterization of eight putative short-chain TIDS proteins revealed that CcTIDS3 and CcTIDS9 exhibit farnesyl diphosphate synthase (FPPS) activity, while CcTIDS1 and CcTIDS2 encode geranylgeranyl diphosphate synthases (GGPPS). Although, CcTIDS8 and CcTIDS10 were found to be catalytically inactive alone, they were able to bind to each other to form a heterodimeric functional geranyl diphosphate synthase (GPPS) in vitro, and this interaction was confirmed using a yeast two-hybrid assay. Furthermore, transcriptome analysis revealed that the CcTIDS3, CcTIDS8, CcTIDS9, and CcTIDS10 genes were found to be more active in C. camphora roots as compared to stems and leaves, which were verified by quantitative real-time PCR (qRT-PCR). These novel results provide a foundation for further exploration of the role of the TIDS gene family in camphor trees, and also provide a potential mechanism by which the production of camphor tree essential oil could be increased for pharmacological purposes through metabolic engineering.